Language lateralisation after Melodic Intonation Therapy: an fMRI study in subacute and chronic aphasia. Issue 7 (3rd July 2018) - van de Sandt-Koenderman, Mieke WME; Mendez Orellana, Carolina P.; van der Meulen, Ineke; Smits, Marion; Ribbers, Gerard M.
ABSTRACT: Background : There is an ongoing debate whether the effect of Melodic Intonation Therapy (MIT) in patients with severe non-fluent aphasia depends on recruitment of right hemisphere (RH) structures for language functioning or on re-recruitment of left hemisphere (LH) language structures. So far, neuroimaging studies have produced conflicting evidence. Aims : To investigate whether a shift in language lateralisation occurs after intensive treatment in subacute (<3 months post onset) and chronic (>1 year post onset) stroke patients with aphasia. Method & Procedures : In a multiple case pilot study with pre-post-design 5 subacute and 4 chronic stroke patients received intensive MIT (6 weeks, 30 sessions). Pre- and post-treatment they underwent functional MRI scanning with a passive listening task to determine language lateralisation indices (LIs). Outcomes & Results : No consistent shift of language activation was found either to the LH or to the RH. With one exception, subacute patients showed symmetrical or right-lateralised language activation pretreatment, which tended to become more right lateralised after treatment. Language activation in chronic patients was left lateralised in two of the four participants, with a tendency towards stronger left lateralised activation after treatment. Conclusions : Data for the subacute patients provide some support for the classical notion that MIT promotes recruitment of RH structures for language processing. However, the contrasting activation patterns in chronic participants before as well as after treatment suggest that reorganisation of language after MIT occurs in interaction with a dynamic recovery process after stroke. Time post onset should be addressed systematically in studies of treatment-induced language recovery.